Corticosteroids and immunosuppressive therapy influence the result of QuantiFERON TB Gold testing in inflammatory bowel disease patients - Ulf Helwig; Michael Müller; Jürgen Hedderich; Stefan Schreiber (2011)
Latent tuberculosis infection is detected by the tuberculin skin test before treating with anti-Tumour-Necrosis factor alpha (anti TNFα) reagents. More accurate are Interferon gamma release assays (IFNγ release assays) to identify patients with latent tuberculosis. Because of a positive control in this assay, it is possible to identify those patients in which a result of tuberculosis testing is not available due to a lack of stimulation capacity of lymphocytes (indeterminate result). Patients suffering from IBD are often treated with immunosuppressive agents, which may influence the results of tuberculosis testing.The aim is to investigate the influence of immunosuppressive agents on the outcome of IFNγ-release assay.50 consecutive patients were documented before introducing anti-TNF-treatment in this single centre study between April 2009 and April 2010. Data of INFγ release assay for latent tuberculosis, skin test and laboratory data and current medication were enrolled.For the period of one year data of 45 consecutive patients was available for statistical analysis. 24 patients out of 45 (corresponding to 53.3%) received at least low doses of corticoid treatment and 27 patients out of 45 (corresponding to 60.0%) received immunosuppressive agents. 13 patients out of 45 (corresponding to 28.9%) had an indeterminate result of the QuantiFERON test. A correlation between the indeterminate result and combination therapy of corticosteroids was found. The concomitant therapy of immunosuppressive agents lead to a lower IFN release but no significance was found.Steroid treatment and further combination therapy with immunosuppressive agents lead to a high risk of indeterminate QuantiFERON test.